Entrepreneurial Intention Of University Student In Medan City With Structural Equation Model (Sem) Approach - Edy Sahputra Sitepu; Azhar Azhar (Proceeding International Seminar of Islamic Studies, 2019)
This paper manifests intentional student entrepreneurship intention model. The purpose of this study is to build a model of entrepreneurial desire influenced by exogenous and endogenous factors. Exogenous factors consist of intellectual intelligence, emotional intelligence, creativity, moral obligation and social support. Whereas endogenous variables consist of attitudes towards entrepreneurship, subjective norms and perceived behavioural control. This research was conducted on students who are studying at the final level from various higher education institutions in Medan. Samples were taken by purposive random sampling totalling 466 students. The data analysis was performed using path analysis and structural equation model (SEM) with Amos Version 22 software. The results of this study indicate that exogenous variables, including intellectual intelligence, emotional intelligence, creativity, moral obligation and social support, affect directly or indirectly. towards endogenous entrepreneurial intention variables for final year students in Medan. The attitude variable toward entrepreneurship, subjective norm and perceived behavioural control in this study can be intervening for the variables of intellectual intelligence, emotional intelligence, creativity, moral obligation and social support in influencing the final level of entrepreneurial intention in Medan City.